Compression and Shear Fracture Analysis of Boundary Cracks Containing Water in Rock - Zhensheng Yang; Fulin Li; Tianran Ma (Advances in Materials Science and Engineering, 2020)
In order to conserve the water resource during underground mining, the fracture and mechanical properties of rock are important for the stability of water-resisting layers, especially for the fracture behavior of boundary cracks containing water in rock. Considering the swelling of rock under water environment and the influence of water on rock, the stress intensity factors of modes I and II are derived for boundary cracks in rock under compressive and shear stresses. The cracks are divided into the closed and open states. The effects of the crack inclination angle, friction coefficient between crack surfaces, and initial crack length on stress intensity factors are also taken into account. The stress intensity factors for closed and open boundary cracks are verified by numerical and physical experiments, respectively, and the deviation of the results is within 5%. It is shown that pore pressure has different effects on the relationship between stress intensity factor and friction coefficient under different lateral pressures. The effect of water on crack propagation is mainly due to the deterioration of the fracture toughness of the rock. It is found that the critical coefficient λc is a key parameter to determine whether the boundary crack propagates in rock under compression-shear stress. Further studies should be performed to apply the present fracture theory to rock mass or water-resisting layers.